Development of a Digital Platform Prototype, to Facilitate Inclusive Learning for Children with Special Needs - Rian Andrian Andrian; Aldi Yasin; Muhammad Raihan Ijlal Hanan; Muhamad Irwan Ramadhan; Taufik Ridwan; Rizki Hikmawan (JOIN (Jurnal Online Informatika), 2022)
Persons with disabilities have the same rights and responsibilities as citizens. Based on the 1945 Constitution Republic of Indonesia, article 31 paragraph 1 and Law Number 20 of 2003 concerning the National Education System, it can be concluded that the state provides full guarantees for Children with Special Needs to obtain quality education services. Many of the problems of inclusive learning that occurred during the Covid-19 pandemic, ranging from the unpreparedness of the school to various problems with environmental factors so that innovation was needed to overcome these problems. In this article, the author develops a prototype of a digital-based learning platform as a solution to facilitate inclusive learning for children with special needs.